2016
DOI: 10.2337/dc15-2137
|View full text |Cite
|
Sign up to set email alerts
|

Text Message Support for Weight Loss in Patients With Prediabetes: A Randomized Clinical Trial

Abstract: OBJECTIVEAlthough the benefits of in-person Diabetes Prevention Program (DPP) classes for diabetes prevention have been demonstrated in trials, effectiveness in clinical practice is limited by low participation rates. This study explores whether text message support enhances weight loss in patients offered DPP classes. RESEARCH DESIGN AND METHODSEnglish-and Spanish-speaking patients with prediabetes (n = 163) were randomized to the control group, which only received an invitation to DPP classes as defined by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
140
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(144 citation statements)
references
References 22 publications
2
140
1
1
Order By: Relevance
“…We read with great interest the article by Fischer et al (1) that was recently published in Diabetes Care. Although we congratulate the authors for their encouraging findings on the impressive role of text messaging support for weight loss management in prediabetes, their results raise several important concerns.…”
mentioning
confidence: 81%
“…We read with great interest the article by Fischer et al (1) that was recently published in Diabetes Care. Although we congratulate the authors for their encouraging findings on the impressive role of text messaging support for weight loss management in prediabetes, their results raise several important concerns.…”
mentioning
confidence: 81%
“…We thank Afarideh et al (1) for their thoughtful discussion of our study of text message support for weight loss in patients with prediabetes (2). We agree that the differential impact by language of the text message intervention was striking and merits further exploration.…”
mentioning
confidence: 95%
“…Indeed, other studies have observed changes in behavior related to daily reminders. 3 As a result, these results also raise the question of how feedback could be optimized to achieve behavior change.…”
mentioning
confidence: 99%